Concentrações de metais pesados em sedimentos fluviais de leito como sinalizadores de pressões antrópicas no entorno do Parque Nacional do Caparaó - William Fortes Rodrigues (2015)
Environmental studies in Brazilian protected areas, especially the management plans have been developed, for the most part, within the protected areas. In general, do not take into account the interfaces with its surroundings, made up of areas called Buffer Zone, where there are human activities that may affect the protected area. From the point of view that includes the buffer zone of Caparaó National Park is a territorial unit, a study of the current situation of natural conditions and human activities developed it is appropriate because these factors may affect the environmental quality of the park. Therefore, the main objective of this study was to evaluate the influence of natural factors and human pressures in the buffer zone of Caparaó National Park and its relation with the quality of river sediments. To make this goal, sediments were sampled at 45 points between the interior and the eastern and western edges of the buffer zone during the wet season. In the field, were determined physico-chemical parameters such as pH and temperature. In the laboratory, set up the particle size distribution, mineral composition by XRD and the total chemical composition by XRF and the available elements ( Co, Cr, Cu, Ni, Zn, Pb , Cd) of extracts with deionized water and 10% HNO3 acid. The chemical opening were made with a microwave oven following the standard method SW-846-3051 - US EPA. The sediments are mainly classified as sandy sediments with 94 % of medium sand. By XRD, the sediments are mainly composed of quartz, muscovite, clay minerals (kaolinite, gibbsite), iron oxides (goethite) and titanium oxide (anatase and rutile). As for the total chemical composition, the highest levels were aluminum oxides. Through ICP-OES analysis, it was determined high point concentration of Cr (236.3 mg/kg), Cu (1.270 mg/kg), Ni (41.92 mg/kg) Zn (589 mg/ kg) Pb (119.3 mg/kg), the highest concentrations were recorded west edge of the park. Then, these levels were compared with the limits established by Resolution CONAMA 344/04. They enroll the above level II, are therefore classified as threshold above which provides a likely adverse effect on the biota. The high levels of the concentrations have close relationship with human activities in the study area, such as coffee, pasture and fish, therefore these results call for a monitoring program and a further study to study area and thus facilitate the impact assessment environmental.